2020
DOI: 10.1021/acs.nanolett.9b05323
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic and Extrinsic Defect-Related Excitons in TMDCs

Abstract: We investigate an excitonic peak appearing in low-temperature photoluminescence of monolayer transition metal dichalcogenides (TMDCs), which is commonly associated with defects and disorder. First, to uncover the intrinsic origin of defect-related excitons, we study their dependence on gate voltage, excitation power, and temperature in a prototypical TMDC monolayer, MoS2. We show that the entire range of behaviors of defect-related excitons can be understood in terms of a simple model, where neutral excitons a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
89
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(103 citation statements)
references
References 65 publications
6
89
1
Order By: Relevance
“…Vacancies introduce a deep center with sharp optical emission, markedly different from previously observed broad luminescence bands. [4][5][6][7][8] Comparing annealed vs. He-ion treated MoS 2 , we establish that the recently discovered single-photon emitters in He-ion irradiated MoS 2 originate from chalcogen vacancies 3 . The latter can be deterministically created with a precision below 10 nm 9 , underscoring the potential of defect engineering for two-dimensional (quantum-) optoelectronics.…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…Vacancies introduce a deep center with sharp optical emission, markedly different from previously observed broad luminescence bands. [4][5][6][7][8] Comparing annealed vs. He-ion treated MoS 2 , we establish that the recently discovered single-photon emitters in He-ion irradiated MoS 2 originate from chalcogen vacancies 3 . The latter can be deterministically created with a precision below 10 nm 9 , underscoring the potential of defect engineering for two-dimensional (quantum-) optoelectronics.…”
Section: Introductionsupporting
confidence: 55%
“…Nevertheless, there is a surprising lack of consensus about the origin for such broad defect emission. Some studies emphasized radiative recombination at intrinsic point defects as underlying mechanism 4,7 . Other studies highlighted the relevance of molecular adsorbates.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was reported that the portion of X D gradually increased during the O2 deposition process until oxygen adsorption was saturated ( Fig. 3(b)) [48]. This gas-ambient influence can be elucidated from two aspects.…”
Section: Defect-bound Exciton Emissionmentioning
confidence: 91%
“…Many defective TMDC samples have been reported to present X D peaks. Upon argon/oxygen plasma [46,47], thermal annealing [17,48], α-particle irradiation [16] or electron beam lithography treatment [49], defects can be introduced intentionally. Additionally, low power treatments typically induce chalcogen vacancies because of their lowest formation energy, whereas more complex defects could be introduced via higher energy or longer treatment times.…”
Section: Defect-bound Exciton Emissionmentioning
confidence: 99%
“…[17,98,99] Among all the matchless properties, their tunable bandgap is really complimentary that conveyed by strong PL and high excitonic binding energy, which makes them an exciting choice for a variety of optoelectronics including solar cells, LEDs, photodetectors, phototransistors, and photoelectric modulators. [19,38,43,100] Exemplify as, distinctive properties of MoS 2 comprising direct bandgap (1.8 eV, see Figure 3a), high charge mobility (≈700 cm 2 V −1 s −1 ), high current on/off ratio (≈10 7 -10 8 ), high optical absorption in visible range (≈10 7 m −1 ), and a giant rising of PL phenomenon from direct bandgap in case of a monolayer; consequently it is thoroughly researched for electronics and optoelectronics. [17][18][19]106] Electrons in crystals show honeycomb configuration structure own a couple of in-equivalent valleys in k-space electronic structure by an extra degree of freedom.…”
Section: Structural Chemistry Of Tmdcsmentioning
confidence: 99%